The Tehêy de Pescaria do Conhecimento by indigenous teacher Dona Liça Pataxoop as a methodology for defending the body-territory of the women of Abya Yala (Praxis Educativa, 2024)
Faced with the violence produced by coloniality and the resistance woven by the multiplicity present in the body-territory of indigenous and black women. This article seeks to reflect on the contributions of the writings of the Tehêy de Pescaria do Conhecimento by indigenous teacher Dona Liça Pataxoop to the weaving of research committed to knowledge, ancestral memories and the body-territory of indigenous and black women. In this study, the act of "Tehêyá" is seen as a form of literacy for the political and subjective formation of the body-territory, as well as a methodological device for "sharpening our gaze", to think of alternatives that can connect the various worlds that have been fragmented by the Modern/Colonial System. We conclude that Tehêy de Pescaria do Conhecimento positions itself as an intersectional, embodied, localized and autobiographical way of knowing.  These positions reaffirm ethical and methodological frameworks committed to the voices of the women of Abya Yala and also question the objectivity defended by the traditional sciences.
Keywords: Tehêy de Pescaria do Conhecimento; decolonial feminism; scientific methodologies; indigenous women; black women